2021
DOI: 10.1177/11206721211035616
|View full text |Cite
|
Sign up to set email alerts
|

Role of anaesthesia in endoscopic and external dacryocystorhinostomy: A meta-analysis of 3282 cases

Abstract: Distal acquired lacrimal obstruction is a common adulthood pathology whose primary treatment is represented by EXT-DCR and END-DCR. When considering their influencing factors, the role of the type of anaesthesia applied during these surgeries has a major role. The aim of this study is to systematically analyse the influence of general and local/regional anaesthesia on the final success rates of EXT-DCR and END-DCR. Primary EXT-DCR and END-DCR articles published later than 2000 with at least 50 single clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…General anaesthesia, although a more costly affair, is indicated in children, if the procedure is timeconsuming or painful, or when local anaesthesia is not possible or due to patient preference [24]. In our study, general anaesthesia was performed more in oculoplastic surgeries, which include external and endoscopic dacryocystorhinostomies, which shows a similar trend as other studies [25,26].…”
Section: Discussionsupporting
confidence: 81%
“…General anaesthesia, although a more costly affair, is indicated in children, if the procedure is timeconsuming or painful, or when local anaesthesia is not possible or due to patient preference [24]. In our study, general anaesthesia was performed more in oculoplastic surgeries, which include external and endoscopic dacryocystorhinostomies, which shows a similar trend as other studies [25,26].…”
Section: Discussionsupporting
confidence: 81%
“… 27 , 28 In this regard, a recent meta-analysis that compared END-DCR performed with general and local anesthesia demonstrated that even in cases where powered instruments were used the procedure in local anesthesia provided good functional success rates, that seems to be slightly different to GA ( p = 0.048): however, due to the low number of available publications, no conclusive statements were made. 29 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, local anesthesia, particularly during an endoscopic approach, can cause several adverse events such as perforation of the eyeball, retro-orbital bleeding, damage to the optical nerve, burning of nasal fossa due to peri-procedural application of diathermy during oxygen supply, and discomfort of trickling blood into the throat, which can be occasionally dangerous in patients with altered sensorium secondary to sedation. 29 In addition, in uncollaborative patients operated with END-DCR in local anesthesia, there is the risk of difficult visualization of the surgical field through the endoscopic instrumentations, thus undermining the final outcome. 25 , 26 , 30 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations